Listening to the Other - Östersjö, Stefan (Book collections on Project MUSE., 2020)
Our contemporary, globalised society demands new forms of listening. But what are these new forms? Stefan Östersjö challenges conventional understandings of the ways musicians listen. He develops a transmodal understanding of listening that is situated in the body - a body that is extended by its mediation through musical instruments and other technologies. Listening habits can turn these tools - and even the body itself - into resistant objects or musical Others. Supported by extensive multimedia documentation and drawing on examples from the author's own artistic projects spanning electronics, intercultural collaboration, and ecological sound art, this volume enables musicians to learn how to approach musical Others through alternative modes of listening and allows readers to discover artistic methods for intercultural collaboration and ecological sound art practices. This book is closely linked to a series of cutting-edge artistic works, including a triple concerto recorded with the Seattle Symphony and several video works with ecological sound art. It represents the analytical outcomes of artistic research projects carried out in Sweden, the UK, and Belgium between 2009 and 2015.